EFEKTIFITAS PEMBUATAN TANAMAN VEGETATIF DALAM MENANGGULANGI EROSI DAN SEDIMENTASI (Studi kasus di daerah aliran sungai Limboto Provinsi Gorontalo). - Iswan Dunggio; Andi Chairil Ichsan (Jurnal Belantara, 2022)
Mostly, there are many factors that cause erosion as follow rainfall, construction and agricultural activities. All these factors refered to uncontrol human activities. The global impacts erosion and sedimentation include disturbance ecosystem, sedimentation in rivers basins and reservoirs and increase emission potential. High erosion can be reduce soil nutrient, organic matters and water availability. The study used USLE method to determine erosion and sedimentation. To measure the effectiveness vegetative planting, we used spatial analysis. The result of spatial analysis show that around 8.58 ton/year of sediment in Limboto lake. The result sediment from Alo Sub-Watershed, Molamahu, Pulubala and Batulayar that contribute sediment around 3.8 million tons/year in Limboto watershed. In region of northern and southern sub watershed such as Pone, Marisa, Biyonga, Talumelito, Tulandenggi, Pilolalenga, Payunga and Tabongo that contribute erosion dan sediment around 5,95 ton/year in Limboto lake, Topodu rivers and Tomini Bay. According erosion classification, Limboto watershed area is dominated very heavy erosion around 29.28%. To control erosion and sedimentation, the land should be restoration reaches 55.82% or 49.892 ha through re-vegetation around 18.30% or 16.362 and develop agroforestry system around 37.51% or 33.530 ha of total Limboto watershed area. The effectiveness of activities revegetation and develop agroforestry system is able to control erosion until 89.56%